Private Investment in Sub-Saharan Africa in the First Half of 2011 Increased Compared to Recent Years - Nicholas, Alexander (World Bank, Washington, DC, 2013)
In the first semester of 2011, three new projects reached financial closure in Sub-Saharan Africa, representing investment commitments of US$697 million. Investment in the first semester of 2011 increased by 27 percent compared with the first semester of 2010, and has risen steadily since the financial crisis of 2008. By number of projects, activity in 2011 decreased by 50 percent compared with the first semester of 2010 indicating fewer, larger projects. The three projects in Sub-Saharan Africa were notable for their use of financial products from multilateral and bilateral agencies.